managerial effectiveness in the formation of high performance teams pesrpectiva from the university of organizations (Revista Electrónica REDINE, 2018)
This article refers to the importance of the effectiveness of the manager in the directionality of the university organization for efficient in their work teams. The purpose is to determine the effectiveness of management in the formation of high performance teams, since it is no secret that managers or leaders lead their subordinates, as part of his team, to which, in often, such personnel do not feel, which is taken into account by them. Maybe so in managerial praxis few changes on the real profile and actions of the manager observed. The methodology is documentary, based on a bibliographic research design in which the information sources used are high, such as books and journal articles and managed to reflect on the appropriate guidelines to manage proactive effects
Keywords: effectiveness; management; organizations